Development and Optimization of Ferrous Fumarate Chewable Tablets by Simplex Experimental Design: Ferrous fumarate chewable tablet formulation by experimental design - Hosseinali Tabandeh; Mohammad Erfan (Iranian Journal of Pharmaceutical Sciences, 2013)
Chewable ferrous fumarate tablet is the best iron dosage form for children due to better compliance and lower teeth staining compared to the oral drop. Because of the different desirable properties of chewable tablets and the opposing effects of fillers on them, the mathematical experimental design was used as the formulation approach. Different series of formulations based on single filler (Lactose granule, mannitol granule, and three Avicels) were prepared and evaluated. The total filler percentage in formulation was kept constant at 40% and simplex lattice mixture design was used with percentages of each of the three selected fillers as factors and hardness, friability, and taste of the resulted tablets as responses. The statistical analysis and optimization were performed by Design Expert software using responses in suggested experimental runs. Two-way analysis of variance and Scheffe Post-Hoc test showed that both the type and amount of fillers were effective on hardness and had interaction. Avicel PH301 was selected as the filler for imparting higher hardness, and lactose and mannitol granules for imparting good taste and mouth feel to tablets. The proper models for the relationship between the three factors and each of the three responses were determined and the regarding equations were suggested. The mathematical optimization suggested the acceptable formulations of ferrous fumarate chewable tablets. The mathematical experimental design is suggested as a promising efficient method for optimization of pharmaceutical formulation projects with multiple goals.